(untitled) (Lex localis - Journal of Local Self-Government, 2024)
The article explores the growing trend of fiscal recentralization in Polish local finance, evident in the increase of intergovernmental transfers, leading to expanded budgetary expenditures, known as the "Flypaper Effect" (FPE). It aims to identify the causes and extent of the FPE in Polish municipalities and cities with county rights from 2010 to 2020, using descriptive and panel data analyses. Empirical research confirms the presence of the FPE in Polish local governments, more pronounced in rural municipalities than in urban counterparts and cities with county rights. The rise in public budgetary expenditures results from limited fiscal autonomy and the ongoing process of recentralization in public finance, further amplifying the FPE. The strength of the FPE varies depending on the specific types and characteristics of intergovernmental transfers. Additionally, the article highlights significant flaws in Poland’s local funding legislation and its consequences, proposing potential paths for local finance reforms. In conclusion, it underscores the increasing trend of fiscal recentralization in Polish local finance driven by the FPE and emphasizes the pressing need for reforms to address these challenges.